2005
DOI: 10.1364/ao.44.000701
|View full text |Cite
|
Sign up to set email alerts
|

Extending the imaging volume for biometric iris recognition

Abstract: The use of the human iris as a biometric has recently attracted significant interest in the area of security applications. The need to capture an iris without active user cooperation places demands on the optical system. Unlike a traditional optical design, in which a large imaging volume is traded off for diminished imaging resolution and capacity for collecting light, Wavefront Coded imaging is a computational imaging technology capable of expanding the imaging volume while maintaining an accurate and robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Honeywell Technologies registered a patent [3] of a similar system capable of performing at-adistance iris recognition. Previously, Fancourt et al [4] showed that it is possible to acquire images at-a-distance of up to 10 meters with sufficient quality to support iris recognition and Narayanswamy and Silveira [5] increased the iris image depthof-field through a simple framework composed by a camera with fixed focus, without a zoom lenses. Park and Kim [21] proposed an approach to fast at-a-distance acquisition of iris images and He et al [6] studied the acquisition of in-focus images, as well analyzed the impact of different wavelengths in the recognition error rates.…”
Section: A Less Constrained Image Acquisitionmentioning
confidence: 99%
“…Honeywell Technologies registered a patent [3] of a similar system capable of performing at-adistance iris recognition. Previously, Fancourt et al [4] showed that it is possible to acquire images at-a-distance of up to 10 meters with sufficient quality to support iris recognition and Narayanswamy and Silveira [5] increased the iris image depthof-field through a simple framework composed by a camera with fixed focus, without a zoom lenses. Park and Kim [21] proposed an approach to fast at-a-distance acquisition of iris images and He et al [6] studied the acquisition of in-focus images, as well analyzed the impact of different wavelengths in the recognition error rates.…”
Section: A Less Constrained Image Acquisitionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] Nevertheless, it has been shown that cubic and trefoil-shaped phases are most used to achieve high-quality images when spherical aberration, 10,11) astigmatism 14,15) and high orderaberrations 15) are also present in the system. WFC can be found in many different applications such as in ophthalmic optics, [15][16][17] iris recognition, 18,19) complexity reduction in optical systems, 20) control of thermal defocus in infrared systems, 21) barcode reading, 22) and microscopy, 23) among many others. The DOF in each application can be extended by a trefoil phase at the exit pupil of the optical system, and the trade-off between the DOF and the image resolution properties is dependent on the peak-to-valley value (strength) of the phase.…”
Section: Introductionmentioning
confidence: 99%
“…Many applications may benefit from extended DOF capabilities in macroscopic imaging, for example in surveillance, machine vision or biometrics problems where the DOF extension is a clear advantage [2,3]; but the technique can also be used to reduce system complexity [4] or for athermalisation and achromatisation of infrared imaging systems [5].…”
Section: Introductionmentioning
confidence: 99%